2013
DOI: 10.1111/jnc.12304
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of excitatory neurotransmission underlying synapse failure in Alzheimer's disease

Abstract: Alzheimer′s disease (AD) is the most common form of dementia in the elderly. Memory loss in AD is increasingly attributed to soluble oligomers of the amyloid-b peptide (AbOs), toxins that accumulate in AD brains and target particular synapses. Glutamate receptors appear to be centrally involved in synaptic targeting by AbOs. Once bound to neurons, AbOs dysregulate the activity and reduce the surface expression of both N-methyl-D-aspartate (NMDA) and 2-amino-3-(3-hydroxy-5-methyl-isoxazol-4-yl)propanoic acid (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(131 citation statements)
references
References 149 publications
(308 reference statements)
5
119
0
1
Order By: Relevance
“…12, 13, 14, 15, 16, 17 Accordingly, memantine (an open-channel blocker of NMDARs) has been approved for clinical use in patients with moderate-to-severe AD. 18 d -serine is the main co-agonist at NMDARs in frontal brain areas 19, 20, 21 and has been implicated in NMDAR-mediated neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…12, 13, 14, 15, 16, 17 Accordingly, memantine (an open-channel blocker of NMDARs) has been approved for clinical use in patients with moderate-to-severe AD. 18 d -serine is the main co-agonist at NMDARs in frontal brain areas 19, 20, 21 and has been implicated in NMDAR-mediated neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…One of the proposed mechanisms for SAD is the amyloid hypothesis, which suggests that deposition of beta-amyloid (Aβ) is a primary event in the pathological cascade for SAD [4]. The balance between the expression and the degradation of Aβ changes, and aggregate of Aβ would cause complex reactions, such as phosphorylation of protein Tau [5], loss of neurotransmitter [6] and finally formation of senile plaques (SP), as well as intracellular neurofibrillary tangles.…”
Section: Introductionmentioning
confidence: 99%
“…No studies have yet demonstrated a conclusive elevation in astrocytic production of D-Serine itself in schizophrenia, and genetic mutations common to this disorder are in fact correlated with diminished levels of astrocytic D-Serine in animal models (Ma et al, 2013, Abazyan et al, 2014. In contrast to schizophrenia, conditions such as Alzheimer's disease and epilepsy are characterised by increased levels of serine racemase and D-Serine in hippocampus, and subsequent overactivation of NMDARs (Ryu et al, 2010, Clasadonte et al, 2013, Paula-Lima et al, 2013, Madeira et al, 2015.…”
Section: D-serinementioning
confidence: 90%